2023
DOI: 10.1021/acsmedchemlett.2c00487
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Annealing Designs Nonhemolytic Antimicrobial Peptides in a Discrete Latent Space

Abstract: Increasing the variety of antimicrobial peptides is crucial in meeting the global challenge of multi-drug-resistant bacterial pathogens. While several deep-learning-based peptide design pipelines are reported, they may not be optimal in data efficiency. High efficiency requires a wellcompressed latent space, where optimization is likely to fail due to numerous local minima. We present a multi-objective peptide design pipeline based on a discrete latent space and D-Wave quantum annealer with the aim of solving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…19–21 Regarding AMP designs, several studies have been reported using Bayesian optimisation combined with machine learning (ML)-based evaluations rather than experimentation. 22,23 However, the optimisation potential of AMPs using Bayesian optimisation combined with experimental feedback has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…19–21 Regarding AMP designs, several studies have been reported using Bayesian optimisation combined with machine learning (ML)-based evaluations rather than experimentation. 22,23 However, the optimisation potential of AMPs using Bayesian optimisation combined with experimental feedback has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21] Regarding AMP designs, several studies have been reported using Bayesian optimisation combined with machine learning-based evaluations rather than experimentations. 22,23 However, the optimisation potential of AMPs using Bayesian optimisation combined with experimental feedback has not been investigated.…”
Section: Introductionmentioning
confidence: 99%